2014
DOI: 10.11648/j.jfa.20140201.12
|View full text |Cite
|
Sign up to set email alerts
|

The Flow of Islamic Finance and Economic Growth: an Empirical Evidence of Middle East

Abstract: Islamic finance is one of the fastest growing sectors of the global banking industry and has risen to prominence recently through its distinctive characteristics. The emergence of Islamic finance can be traced back to 1963 in Egypt, while its importance comes to the global financial system only after the global financial crisis occurred in 2008. This paper explores empirically the relationship between the development of Islamic finance and economic growth in the Middle East. Three of the most important countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 13 publications
3
30
0
1
Order By: Relevance
“…transactions, and it is confirmed that Islamic banking has contributed to the growth of the economies(Tabash & Dhankar, 2014). The current study shows the impact of Ramadan on the Islamic stock market.…”
supporting
confidence: 75%
“…transactions, and it is confirmed that Islamic banking has contributed to the growth of the economies(Tabash & Dhankar, 2014). The current study shows the impact of Ramadan on the Islamic stock market.…”
supporting
confidence: 75%
“…They concluded that Islamic banking contributes to economic growth. Abduh and Omar (2012), Tabash and Dhankar (2014a) and Tabash and Dhankar (2014c) also reached this conclusion with the help of the same method. In addition to those studies, Abduh and Chowdhury (2012), Yazdan and Dastan (2013) and Tabash and Dhankar (2014b) emphasized the similar result with the help of Granger causality analysis.…”
Section: Bsupporting
confidence: 55%
“…Abduh and Omar (2012), Tabash and Dhankar (2014a) and Tabash and Dhankar (2014c) also reached this conclusion with the help of the same method. In addition to those studies, Abduh and Chowdhury (2012), Yazdan and Dastan (2013) and Tabash and Dhankar (2014b) emphasized the similar result with the help of Granger causality analysis. Furthermore, Kassim (2016) and Yazdan and Sadr (2012) used ARDL test and determined that there is a strong relationship between Islamic finance and economic growth.…”
Section: Bsupporting
confidence: 55%
“…Tabash and Dhanker (2013) have highlighted an enduring 29 % growth in assets of the Islamic finance industry from 2000 to 2011, despite the financial crisis and political turmoil that characterized this span of years. As Tabash and Dhankar (2014) have demonstrated, the expansion of the Islamic financial system has had, and will likely continue to have, positive repercussions on overall economic growth.…”
Section: Increased Trade Between Western and Predominantly Muslim Coumentioning
confidence: 96%